Application of Quasi-Subordination for Generalized Sakaguchi Type Functions. (31st October 2017) - Altınkaya, Şahsene
Abstract : The author constructs a new class S q λ G, s, t of univalent functions applying the Ruscheweyh derivative. Moreover, the coefficient estimates including a Fekete-Szegö inequality of this class were determined.